A Novel Mutation in FOXC1 in a Lebanese Family with Congenital Heart Disease and Anterior Segment Dysgenesis: Potential Roles for NFATC1 and DPT in the Phenotypic Variations - Khalil, Athar; Al-Haddad, Christiane; Hariri, Hadla; Shibbani, Kamel; Bitar, Fadi; Kurban, Mazen; Nemer, Georges; Arabi, Mariam (Frontiers in Cardiovascular Medicine, 2017)
Congenital heart diseases (CHDs) are still the leading cause of death in neonates. Anterior segment dysgenesis is a broad clinical phenotype that affects the normal development of the eye, leading in most of the cases to glaucoma which is still a major cause of blindness for children and adolescents. Despite tremendous insights gained from genetic studies, a clear genotype-phenotype correlation is still difficult to draw. In Lebanon, a small country with still a high rate of consanguineous marriages, there is little data on the epidemiology of glaucoma amongst children with or without CHD. We carried out whole exome sequencing (WES) on a family with anterior segment dysgenesis, and CHD composed of three affected children with glaucoma, two of them with structural cardiac defects and three healthy siblings. The results unravel a novel mutation in FOXC1 (p. R127H) segregating with the phenotype and inherited from the mother, who didn’t develop glaucoma. We propose a digenic model for glaucoma in this family by combining the FOXC1 variant with a missense variant inherited from the father in the Dermatopontin gene (DPT). We also unravel a novel NFATC1 missense mutation predicted to be deleterious and present only in the patient with a severe ocular and cardiac phenotype. This is the first report on FOXC1 using WES to genetically characterize a family with both ocular and cardiac malformations. Our results support the usage of such technology to have a better genotype-phenotype picture for Mendelian inherited diseases for which expressivity and penetrance are still not answered.